THE EFFECT OF PSYCHOLOGICAL STRESS ON THE INCIDENCE OF CANCEROUS TUMORS IN THE SOUTH REGION OF JORDAN - Al-Nawiseh, Zakaria Hussein; Al-Eidi, Khetam Mohammed (European Scientific Journal, ESJ, 2015)
The aim of this study was to identify the effect of psychological stress on the incidence of cancerous tumors in the south region of Jordan. This retrospective study was conducted in educational governmental hospitals between 2007 and 2014. Around 2909 cancer patients from south region of Jordan were included and data collection sheet was filled with all required information for each patient. The results showed a direct positive correlation between psychological stress and incidence of cancerous tumors. In addition, there were no substantial statistical significance (p value ≤0.05) utilize the impact of psychological stress on the incidence of cancerous tumors due to patients’ gender, marital status, and place of residence. In conclusion, psychological stress is one of the main risk factors for the incidence of cancer in south Jordan. Therefore, prospective studies would be of interest to investigate the causal relationship between the psychological stress and the incidence of cancer. Moreover, educational programs and social services to help psychotic patients and also to increase the community awareness toward the psychological stress are required to decease the incidence of cancer in Jordan.